José Godoy Garcia: a voz do modernismo em Goiás - Campos, Ionice Barbosa de (2011)
In this research, we intent, in the first chapters to do a presentation of the writer and poet from Goiás, José Godoy Garcia, considering that he has not got the deserved recognition of the reading public. In this way, we discuss the contribution of the author participation in the modernist movement, which is considered anachronistic in Goiás, confirming the opposite of our initial assumption that it was only a precursor of that school of poetry. In line with Gilberto Mendonca Teles, initially we thought that Garcia Godoy was a anachronistic and parochial writer, however, guided by his text reading and finding harmony between his work and national and international literature, we find an author engaged and aligned literarily and aestheticly. For this, we highlight the characteristic aspects of his writing, as novelist, revealing the peculiarities of his historical novel, in the theoretical perspective of Vera Figueiredo Follain. In addition, we made a brief explanation of his book of short stories and critical works, without further analysis, only in order to show the reader of this research that Godoy Garcia is not just a poet, as we thought, a priori. The writer goiano revealed also be upgraded and a master novelist, short story writer and literary critic, in view of the different thematic approaches that can be found in his style. In a second step, already in the final chapter, we propose a more detailed reading of selected poems that highlight the most significant themes of ―godoyan‖ poetic, making evident the peculiarities: modernist, social and prosaic poetry. According to Antonio Candido, Alfredo Bosi, Emil Staiger and Octavio Paz we understand the characteristics of modernist literature and the concepts of society and the hybridity of literary genres. We understand that all stages of this work have contributed to achieving our main goal, which is to show why José Godoy Garcia deserves to be known beyond Goiás and become a part of the national literary scene.